Reproductive behavior and larval development of the striped blenny Meiacanthus grammistes - Kien, Nguyen Trung; Zeng, Chaoshu (Vietnam Journal of Marine Science and Technology, 2019)
This study aims to describe aspects of reproductive behavior and larval development for the striped blenny, Meiacanthus grammistes. Altogether 8 broodstock fish (8.5 cm to 10 cm) were maintained in two 400 l tanks. The first spawning occurred 45 days in one tank and 65 days in another tank after fish acquisition. Egg clutches were only found attached to inside walls of the 50 mm capped PVC pipes with a single 25 mm reduce entry hole while the male took full responsibility for egg care. The fish spawned routinely every 8–10 days in both tanks throughout experimental period. The fecundity ranged from 500–4,200 eggs per spawning with an average of 1837 ± 1197 eggs/clutch. Newly extruded eggs were spherical and incubation period lasted 203–207 h at 27 ± 1oC. Newly hatched larvae measured 3.11 ± 0.14 mm in standard length (SL) and 0.87 ± 0.08 mm in body depth (BD) with average mouth-gape height and width at 272.42 ± 61.03 µm and 187.50 ± 36.46 µm, respectively. Under such a feeding regime, most of larvae had settled out water column onto the bottom around 23 DPH but not yet displayed the full colouration pattern of adults. In period of 24 to 29 DPH, the colouration pattern developed with alternating black and yellow stripes running through the entire length of body and the newly settled juvenile measured 12.91 ± 0.35 mm in SL and 3.36 ± 0.12 mm in BD around 30 DPH.